Time course of the anticonvulsant action of clonazepam during ontogenesis in the rat - Kubová, H; Mares, P (Archives internationales de pharmacodynamie et de therapie, 1989)
A time course of the protective action of clonazepam against metrazol-induced seizures was studied in 612 rats aged 7, 12, 18, 25 and 90 days. Two doses of clonazepam (0.1 and/or 1 mg/kg) were used and metrazol (100 mg/kg in all but 18-day-old animals where 90 mg/kg were given) was administered s.c. from 30 min to 48 hr. Not all time intervals were examined in all age groups. Eight to 14 rats were used for each time interval, dose and age group. Both doses exhibited a clear-cut antimetrazol action at all developmental stages studied. The protective action lasted longest in the 2 youngest groups and shortened progressively with age. The lower dose of clonazepam always exhibited shorter duration of action than the 1 mg/kg dose. Both doses were more efficient against major than against minimal metrazol seizures in 18-day-old and older rats where minimal seizures could be reliably elicited by metrazol.
Keywords: Anticonvulsants; Pentylenetetrazole; Seizures; antikonvulziva; záchvaty; injekce subkutánní; stárnutí; krysa rodu Rattus; zvířata; Aging; pentylentetrazol; Clonazepam; časové faktory; Injections, Subcutaneous; Male; Rats; klonazepam; Animals; mužské pohlaví; Time Factors